Bioinformatic analysis of the molecular mechanisms underlying the progression of bone defects - Liu, Hao; Zhao, Xuan; Li, Yin; Yi, Jiang; Zhang, Chenxi; Zheng, Ziyang; Dai, Siming; Yin, Guoyong; Zhao, Shujie (Frontiers in Medicine, 2023)
Background The pathophysiology of bone defects (BDs) is complex, and the treatment for bone defects, in particular massive bone defects, remains a major clinical challenge. Our study was conducted to explore the molecular events related to the progression of bone defects a common clinical condition. Methods First, microarray data of GSE20980 were obtained from the Gene Expression Omnibus (GEO) database, where 33 samples in total were used to analyze the molecular biological processes related to bone defects. Next, the original data were normalized and differentially expressed genes (DEGs) were identified. Additionally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted. Finally, a protein–protein interaction (PPI) network was constructed and the trends of the different genes were confirmed. Results Compared with the samples of non-critical size defects (NCSD), the samples of critical size defects (CSD) had 2057, 827, and 1,024 DEGs at 7, 14, and 21 days post injury, respectively. At day 7, the DEGs were significantly enriched in metabolic pathways, at day 14 the DEGs were predominantly enriched in G-protein coupled signaling pathways and the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, and at day 21 the DEGs were mainly enriched in circadian entrainment and synaptic-related functions. The PPI network showed similar results. Quantitative real-time PCR (qRT-PCR) and western blot (WB) were performed to validate the partial results of sequencing. Conclusion This study provides some clues about the molecular mechanism behind bone defects, which should contribute to scientific research and clinical treatment of this condition.